Analysis on the investment of the insurance companies as perceived by its financial managers as basis for portfolio mix strategy - Jena Rose B. Sarol, Cinderella S. Calugay, Marian Abigail L. Peamente, Lheanne Z. Recto, Irish Shane G. Luna, Zyra Anne Saquilayan 4 0 16; 5
ABSTRACT: This research paper presents an analysis on the investment practices of insurance companies in the National Capital Region (NCR) of the Philippines, as perceived by their financial managers. The objective is to provide insights for formulating effective portfolio mix strategies within the insurance industry. The study focuses on examining the profiles of selected life and non-life insurance companies, growth rates of insurance liabilities and allocation of investable funds. and profit rates. Using a descriptive research design, primary and secondary data were collected from financial managers of insurance companies operating in the NCR. The sample consists of a purposive selection of participants, reflecting a diverse range of companies in terms of size, experience, and market presence. Descriptive and inferential statistical analyses are employed to gain a comprehensive understanding of investment practices and their implications. The findings of this research shed light on several important aspects of investment in the insurance industry within the NCR. The majority of the surveyed insurance companies are domestic entities, indicating a high level of expertise and experience within the sample. Their long-standing presence in the industry underscores their stability and reliability, which are crucial factors in investment decision-making. Both the life and non-life insurance sectors are well-represented in the study, demonstrating the industry's commitment to offering comprehensive coverage options. The surveyed companies provide a diverse range of insurance policies, including health, life, and motor insurance, catering to the specific needs of policyholders. The inclusion of new policyholders in significant numbers indicates a positive growth trajectory and suggests a strong market demand for insurance products. Analysis of the growth rates of insurance liabilities reveals varying trends between life and non-life insurance companies. Life insurance companies experience growth rates ranging from 19.5% to 20.5%, emphasizing the importance of adequately preparing for claim settlements. Non-life insurance companies observe growth rates between 14.42% to 15.12%, highlighting the need for effective monitoring of liabilities to ensure policyholders' financial well- being. There was a strong positive correlation between the growth rates of insurance liabilities and insurable risk, indicating an increasing demand for insurance coverage. Insurance companies allocated a significant portion of their investable funds to debt securities and equity securities, with debt securities receiving the highest allocation. The majority of companies reported positive profit rates from their investments in debt and equity securities. These findings provide valuable insights for insurance companies in developing portfolio mix strategies. Factors Such as company profile, growth rates, and investment options should be considered. However, further research is needed to explore additional variables that may impact the insurance industry. This study provides a comprehensive analysis on insurance industry investment practices in the National Capital Region (NCR) of the Philippines, focusing on portfolio strategies, company profiles, liability growth rates, and fund allocation. The findings highlight varying growth rates of insurance liabilities, emphasizing the need for preparation and monitoring. A positive correlation between liability growth rates suggests increasing demand for insurance. The allocation of funds to debt and equity securities with positive profits offers viable investment options, guiding effective portfolio strategies for long-term industry growth and success in the NCR. To further enhance the effectiveness of investment practices in the insurance industry in the National Capital Region (NCR) of the Philippines, it is advisable for insurance companies to continuously monitor and adapt to changing growth rates of insurance liabilities. Additionally, they should consider diversifying their investment portfolios to mitigate risks and explore opportunities for further innovation and technological integration in their investment strategies.
Research Paper: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2